Construction of redox-active multilayer film for electrochemically controlled release - Sun, Yi-xin (Langmuir : the ACS journal of surfaces and colloids, 2013)
An electrochemically controlled drug release from a redox-active multilayer film is reported. The multilayer film is fabricated by alternate assembly of the electrochemical redox-active micelles and DNA. The buildup of multilayer films is monitored by spectroscopic ellipsometry, UV-vis spectroscopy, and fluorescence spectroscopy. A ferrocene-modified poly (ethyleneimine) (PEI-Fc) is used to form a hydrophobic ferrocene core and hydrophilic PEI shell micelle, showing the electrochemical redox-active properties. Hydrophobic pyrene (Py) molecules are then incorporated into the micelles. The PEI-FcPy micelles are assembled into the (PEI-Fc@Py/DNA) multilayer film by layer-by-layer assembly. Thanks to ferrocene groups with the properties of the hydrophilic-to-hydrophobic switch based on the electrical potential trigger, pyrene molecules can be control released from the multilayer film. The electrochemically controlled release of pyrene is investigated and confirmed by electrochemical quartz crystal microbalance and electrochemistry workstation. The (PEI-Fc@drug/DNA) multilayer film may have potential applications in the field of biomedical and nanoscale devices